Exploratory investigation on coking behaviors during preheating/liquefaction of coal-oil slurry. (1st February 2022) - Huang, Sheng; Zhang, Yuanlin; Xu, Chunhui; Wu, Dayu; Xie, XiaoYang; Wang, Zhengxu; Wu, Shiyong; Wu, Youqing; Gao, Jinsheng
Highlights: Coking behaviors during preheating/liquefaction of coal-oil slurry were studied. Effects of temperature and solvent quality on coking propensity were investigated. Temperature and H2 pressure are important factors affecting coking severity. Coking propensity of coal-oil slurry is related to caking property of parent coal. Abstract: In this study, the effects of coal property, solvent quality, H2 pressure, preheating/liquefaction temperature and time on coking behaviors of coal-oil slurry during preheating/liquefaction process were investigated, and effective measures to alleviate the coking propensity were proposed. Results show that preheating/liquefaction temperature is the most significant factor affecting coking severity of coal-oil slurry. At the temperature lower than 450℃, coking is not occurred in the early stage of preheating/liquefaction process, as the reactions proceeds and hydrogen consumption, coking is occurred due to activated hydrogen is insufficient, and coking propensity of coal-oil slurry is tiny/modest. At the temperature higher than 450℃, coking is occurred during the whole preheating/liquefaction process, and the coking propensity is obvious in the hydrogen deficient system. H2 pressure is another important factor that can affect the coking severity of coal-oil slurry, and relatively high H2 pressure can effectively reduce the risk of coking, especially at the relatively high temperature. The coking propensity of three coals in tetralin are higher than that in shenhua recycle oil. Solvent quality significantly affect coking severity of coal-oil slurry, and solvent with high hydrogen-donating and transferring capacity and strong dissolving ability can effectively reduce the coking severity. The ordering for the coking propensity of three coals preheating/liquefaction in tetralin is as follows: Yanzhou coal > Huainan coal > Shenhua coal, which is closely related to the caking properties of parent coal.